EFEKTIVITAS PENGGUNAAN MEDIA BERBASIS APLIKASI SMART SPLIT PADA PEMBELAJARAN MATEMATIKA - Dukei, Nurain; Katili, Sukri; Aries, Nur Sakinah; Arif, Rifda Mardian; Pulukadang, Wiwy Trianty (EDUTECH : Jurnal Inovasi Pendidikan Berbantuan Teknologi, 2025)
The objective of this study is to develop a Smart Split application-based media that meets the criteria of feasibility, practicality, and effectiveness in mathematics learning to improve student learning outcomes on the topics of equivalent fractions and comparing fractions in Grade IV at SDN 16 Telaga Biru, Gorontalo Regency. This study employed a Research and Development (R&D) method using the ADDIE development model, which consists of the stages analyze, design, develop, implement, and evaluate. The feasibility of the Smart Split application-based media was tested through validation by a team of experts. The validation results showed an average percentage score of 93%, categorized as highly feasible for use by teachers and students in elementary schools. To test practicality, the researcher used teacher observation sheets and student response sheets, which resulted in scores of 98.75% and 91.67%, respectively, both classified as highly practical. Regarding media effectiveness, the media implementation in Grade IV at SDN 16 Telaga Biru was measured using pre-tests and post-tests. The results showed that the average pre-test score of 30 increased to 85 33 in the post-test. The N-Gain score was 0.78, which falls into the "high" category. Based on these findings, the Smart Split application-based media is proven to improve student learning outcomes and is effective for use in elementary school learning. ABSTRAKTujuan penelitian ini adalah mengembangkan media Smart Split berbasis aplikasi yang memenuhi kriteria kelayakan, kepraktisan, dan efektivitas dalam pembelajaran matematika guna meningkatkan hasil belajar siswa pada materi pecahan senilai dan membandingkan pecahan di kelas IV SDN 16 Telaga Biru Kabupaten Gorontalo. Penelitian ini menggunakan metode RnD (Research and Development) dengan menggunakan model penelitian pengembangan ADDIE, yang mencakup tahapan analyze, design, development, Implement, dan Evaluate. Kelayakan media Smart Split berbasis aplikasi diuji melalui validasi oleh tim ahli. Hasil validasi menunjukkan bahwa media ini memperoleh rata-rata persentase sebesar 93%, yang dikategorikan sangat layak digunakan oleh guru dan siswa di sekolah dasar. Untuk menguji kepraktisan, peneliti menggunakan lembar observasi guru dan lembar respon siswa, yang menghasilkan masing-masing skor sebesar 98,75% dan 91,67%, masuk dalam kategori sangat praktis. Dalam aspek efektivitas, penerapan media di kelas IV SDN 16 Telaga Biru diukur melalui pre-test dan post-test. Hasilnya, total nilai rata-rata pre-test sebesar 30 meningkat menjadi 85,33 pada post-test. Perhitungan N-Gain menunjukkan skor 0,78, yang tergolong dalam kategori “tinggi.” Berdasarkan hasil ini, media Smart Split berbasis aplikasi terbukti dapat meningkatkan hasil belajar siswa dan efektif untuk digunakan dalam pembelajaran di sekolah dasar.